ChemInform Abstract: Accessing Elaborated 2, 1‐Borazaronaphthalene Cores Using Photoredox/Nickel Dual‐Catalytic Functionalization. Issue 33 (July 2016) - Jouffroy, Matthieu; Davies, Geraint H. M.; Molander, Gary A.
Abstract: A range of borazaronaphthalene derivatives are efficiently and selectively alkylated using ammonium alkylsilicates under base‐free, near‐neutral conditions.